PERTUMBUHAN DAN AKTIVITAS ANTIOKSIDAN DARI MIKROALGA - RAFAELINA, MONIKA; RUSTAM, YOSWITA; AMINI, SRI (Bioma, 2015)
ABSTRACT Microalgaebiomass containschemicalcomponentssuch as vitamin, proteins, Ï‰-3 and Ï‰-6 polyunsaturated fatty acid and pigments. components with antioxidant activities can be found in only a few species of algae. The potential species of microalgae who have compounds act as antioxidant are Porphyridium cruentum and Chlorella sp. This study aimed to know the growth and antioxidant activity of P. cruentum and Chlorella sp. with the treatment of different cultures. Experimental method and completely randomized design was used as the research method. Antioxidant activity (Ic50 value) was measured by DPPH method (2,2-diphenyl-1-pikrilhidrazil). SPSS 16.0 is used to analyze the data with General Linier Model (GLM) Univariate. The results of GLM Univariate test for cell density showed that there was significant different for cell density in species factors (p= 0,000), but there was no significant different for cell density in culture factors (p= 0,375), and GLM Univariate test for antioxidant activity showed that no significant different for antioxidant activity in species factors (p= 0,522) but siginificant different for antioxidant activity in culture factors (p= 0,001). There was significant different for growth in P. cruentum and Chlorella sp. but no significant different in indoor and outdoor culture, as well as there was no significant different antioxidant activity in two species but significant different in indoor and outdoor culture. Keywords: growth, antioxidant activity, indoor cultivation, outdoor cultivation.